When Physical Education Becomes High-Stakes: A Baidu Index Study of Public Online Attention to China’s Zhongkao PE - Zhang, Xiaodan; Yao, Jiali; Teng, Luyan (Quality in Sport, 2026)
Background: In 2020, China issued several national policy documents that emphasized reforming school physical education (PE) and gradually increasing its score weight in the Zhongkao (China’s High School Entrance Examination). This policy shift brought PE into closer connection with high-stakes educational assessment and appears to have generated growing public attention and information-seeking. Objective: This study explores temporal patterns, geographic and demographic distributions in public online search behavior related to Zhongkao PE, following the 2020 national policy of PE assessment. Methods: The Baidu Index platform was used to collect search data for the Chinese keyword “体育中考” (Zhongkao PE) from May 1, 2019, to May 1, 2026. Descriptive analyses were conducted to examine weekly search trends, PC and mobile search patterns, geographic search distribution, and demographic profiles by age and gender. Results: The study results show clear seasonal fluctuations around examination periods and a noticeable increase after 2021. Geographically, search activity was concentrated in coastal and highly urbanized regions. Demographically, users aged 30–49 years accounted for the largest share of searches, followed by users aged ≤19 years. Female users demonstrated more searches than males, although male users showed higher relative concentration. Conclusion: The Zhongkao PE reform was not only an assessment change but also a public information event. Given that high-stakes PE testing can raise public attention to physical education, policymakers should provide clear, health-oriented guidance to keep the reform focused on its original goal for improving student health and promoting physical activity for the long term.